Marital Problem Solving, Marital Offense Forgiveness, Spousal Self-Efficacy as Predictors of Marital Adjustment - Bingöl, Tuğba Yılmaz (Sage, 2026)
Marital adjustment can be conceptualized as a resource of the family system or a part of the regenerative powers of the family. It is important to investigate marital adjustment as it is a concept that deeply affects the quality of life. In this study, which attempts to explain marital adjustment, regression analysis was performed on the obtained results. The data were examined with correlation analysis and regression analysis. According to the study results, there was a strong positive correlation (r = .76) between marital adjustment and spousal self-efficacy among the predictor and dependent variables. Martial adjustment establishes a high level and significant relationship with spouse selfefficacy, resentment-avoidance, marital problem solving, gender, marriage duration, having children and the number of children, income level, education status and place of residence. All variables (spousal self-efficacy, resentment-avoidance, marital problemsolving skills, gender, duration of marriage, having children, number of children, income level, educational status, and place of residence) explain 75% of marital adjustment.
Keywords: Marital Problem Solving; Marital Offense Forgiveness; Spousal Self-Efficacy; Marital Adjustment; Marital Relationship